Biologically effective daily radiant exposure for erythema appearance, previtamin D3 synthesis, and clearing of psoriatic lesions derived from erythemal broadband meters at Belsk, Poland, for the period 1976–2023 - J. W. Krzyścin; A. Czerwińska; B. Rajewska-Więch; J. Jarosławski; P. S. Sobolewski; I. Pawlak (Earth System Science Data)
A long-term series of exposures to solar ultraviolet radiation (UVR) is required to assess the risks and benefits of radiation for different human biological processes. However, homogenisation of the amount of biologically effective solar energy (i.e. energy-weighted according to the sensitivity of the selected biological process to solar radiation) reaching the Earth's surface over long periods is challenging due to changes in measurement methods and instruments. This paper presents the world's longest homogenised time series of biologically effective daily radiant exposures (DRE) from regular monitoring with different erythemal broadband radiometers (EBRs) operated at the Central Geophysical Laboratory of the Institute of Geophysics, Polish Academy of Sciences (IG PAS), Belsk (20.79° E, 51.84° N), from 1 January 1976 to 31 December 2023. The following biological effects were considered: erythema, cutaneous synthesis of previtamin D3, and clearing of psoriatic lesions. The data for the latter two biological effects are estimated based on the proposed method of using EBR measurements to calculate other non-erythemal DRE. The following EBRs were used in the monitoring: Robertson–Berger meter (1975–1992), Solar Light model 501 (1993–1994 with #927, 1995–2013 with #2011), and Kipp & Zonen UV-AE-T #30616 from 5 August 2013 to the present. From 1976 to 2013, the homogenisation procedure consisted of comparing the measured erythemal DRE and daily maximum of UV index (UVIMAX) with the corresponding modelled values from simulations using a radiation transfer model for cloudless conditions. Between 2014 and 2023, the EBR data were compared with data from a collocated reference instrument, the Brewer Mark II #64 spectrophotometer. Such comparisons resulted in a set of multipliers that were applied to the EBR measurements. Two different versions of the homogenisation method were applied, analysing modelled and observed values for erythemal DRE and UVIMAX assuming different criteria for cloudless days. Three regression models of the erythemal data on common UVR proxy data (total column ozone, aerosol optical depth, and global clear-sky irradiance index) were used to reconstruct the UVR data from the beginning of the Belsk observations, allowing further validation of the homogenised UVR data. Linear trends calculated showed a statistically significant increase in erythemal annual and summer (June to August) radiant exposures of about 6 % per decade over the period 1976–2005. Thereafter, no trend was observed. Similar trend estimates were found for all biological effects considered. The data are made freely available via the following repository: https://doi.org/10.1594/PANGAEA.972139 (Krzyścin et al., 2024). An additional version of the re-evaluated data, together with the corresponding clear-sky and proxy data used in the UVR data reconstruction, is archived at https://doi.org/10.25171/InstGeoph_PAS_IGData_Biologically_Effective_Solar_Radiation_Belsk_1976_2023 (Krzyścin, 2024).